Risk factors for coronary artery disease in patients undergoing elective coronary angiography in Jordan - Al-Shudifat, Abdel-Ellah (BMC Cardiovasc Disord, 2017)
BACKGROUND: Unhealthy lifestyle factors such as smoking, obesity, inactivity and type 2 diabetes are endemic in the Middle East. The public health consequences might be detrimental; however, local studies on risk factors for coronary artery disease (CAD) are scarce. METHODS: Patients referred for coronary angiography at a tertiary hospital in Amman, Jordan, between January and December 2015, were included in this study. Risk factors for CAD were assessed in a multivariate logistic regression model, and presented as odds ratio (OR) with 95% confidence interval (CI). RESULTS: Among 557 participants, 356 (63.9%) had CAD and 201 (36.1%) had a normal cardiogram. The majority (n = 395, 70.9%) were male, and median age was 55 years (interquartile range 47–64). Two-hundred-and-fifteen (38.6%) individuals reported previous diabetes, and 287 (51.5%) were current or previous smokers. In multivariate analysis, male gender (OR 3.7, 95% CI 2.3–6.0), age (45–54 years: OR 4.8, 95% CI 2.7–8.5; 55–64 years: OR 6.0, 95% CI 3.2–11.4; ≥65 years: OR 15.7, 95% CI 7.8–31.3), previous diabetes (OR 2.6, 95% CI 1.7–4.1) and current/previous smoking (OR 2.1, 95% CI 1.3–3.4) were significant predictors of CAD. CONCLUSIONS: Age, gender, diabetes and smoking were strong and significant risk factors for CAD in Jordan. Public health interventions to reduce the prevalence of smoking and diabetes are urgently needed.